2022
DOI: 10.16910/jemr.15.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements as a predictor of preference for progressive power lenses

Abstract: The purpose of this study is to determine if there is any correlation between the characteristics of the user’s eye movements (EMs) and the preference of the user when wearing different Progressive power lenses (PPLs) distributions. An eye-tracker system with a sample rate of 120Hz and temporal resolution of 8.3ms (Tobii-X3-120) was used to register EMs of 38 PPL users when reading in a computer screen with 2 types of PPLs (PPL-soft and PPL-hard). Number of fixations, complete fixation time, fixation duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The results showed that reading time and number of fixations were higher when subjects were using PPLs in comparison with single-vision lenses. Another study from Concepcion et al [ 26 ], recorded eye movements using a Tobii X3-120 ET system on 38 presbyopic subjects while using two different PPLs. Subjects were asked to read out loud a text on a computer screen located at 0.67m, at on-axis and off-axis viewing position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that reading time and number of fixations were higher when subjects were using PPLs in comparison with single-vision lenses. Another study from Concepcion et al [ 26 ], recorded eye movements using a Tobii X3-120 ET system on 38 presbyopic subjects while using two different PPLs. Subjects were asked to read out loud a text on a computer screen located at 0.67m, at on-axis and off-axis viewing position.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Han et al [ 24 , 25 ] used ET techniques to determine eye movements differences between PPLs and single-vision lenses. Concepcion et al [ 26 ] analyzed the differences in visual behavior of different visual areas of the PPLs during reading on a computer screen. Rifai et al [ 27 ] evaluated eye and head movements during driving in PPL users in comparison with non-PPL users.…”
Section: Introductionmentioning
confidence: 99%
“…According to TUIK 2021 [1] data, it is stated that the use of glasses or lenses has increased by 2.6% and the number of individuals blind increased by 0.3%. This situation has led manufacturers to increase the number of contact lenses.…”
Section: Introductıonmentioning
confidence: 99%
“…25 Despite MFCLs and PAL spectacles being designed to offer clear vision at all viewing distances, there are relatively few reports in the literature where eye or head movement metrics are investigated across multiple viewing distances. Perhaps due to the additional experimental complexity required to collect measures across multiple distances, published work relating to eye and head movements in presbyopia has largely incorporated either a single viewing distance, such as at near, 24,25 intermediate 22,26 or in some reports, two viewing distances being investigated. 23,27,28 This investigation set out to address this gap in the literature by investigating eye and head movements at three viewing distances (distance, intermediate and near) for SVCLs (acting as a control), MFCLs and PAL spectacles, and to simulate real-world viewing conditions by adopting natural postures and head movements in visually familiar environments.…”
mentioning
confidence: 99%